1992
DOI: 10.1037/0021-9010.77.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of crime-relevant information and the Guilty Knowledge Test.

Abstract: The effects of awareness of crime-relevant information on the detection of deception with the Guilty Knowledge Test were examined. Student subjects were assigned to 1 of 3 groups: a guilty group, members of which committed a mock crime; an innocent group aware of details about the crime; or an innocent group unaware of such information. After following instructions, subjects were tested on the polygraph with a 10-item Guilty Knowledge Test and were offered $20.00 for an innocent test outcome. Skin resistance r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 13 publications
6
61
1
1
Order By: Relevance
“…Results showed that the detection rates of guilty participants by the GAT were higher than those of any innocent group. Additional studies reported similar results (Ben-Shakhar, et al, 1999;Bradley and Rettinger, 1992). However, when deception and knowledge were controlled, and the effect of guilt was examined alone, a very high rate of false positives was reported for informed innocent participants (Bradley et al, 1996).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Results showed that the detection rates of guilty participants by the GAT were higher than those of any innocent group. Additional studies reported similar results (Ben-Shakhar, et al, 1999;Bradley and Rettinger, 1992). However, when deception and knowledge were controlled, and the effect of guilt was examined alone, a very high rate of false positives was reported for informed innocent participants (Bradley et al, 1996).…”
Section: Introductionsupporting
confidence: 57%
“…Studies addressing the issue of leakage of crime-related information in the CIT were able to differentiate knowledgeable innocent participants from guilty ones to different degrees, ranging from the innocents perfect detection to a very high rate of false positive errors (e.g., Ben-Shakhar et al, 1999;Bradley and Rettinger, 1992;Bradley and warfield, 1984;Gamer, 2010;Giesen and Rollison, 1980;Stern et al, 1981). Bradley and Warfield (1984) slightly changed the wording of the question from passive knowledge (e.g., "What was the color of the stolen envelope?")…”
Section: Introductionmentioning
confidence: 98%
“…This study focused on the external validity of the mock-crime paradigm, which has been used extensively in the past 3 decades to evaluate the validity of the GKT (e.g., Ben-Shakhar & Dolev, 1996;Ben-Shakhar et al, 1999;Bradley, MacLaren, & Carle, 1996;Bradley & Rettinger, 1992;Davidson, 1968;Lykken, 1959). We showed that the standard mock-crime procedure, applied in most of these studies, may have weak external validity because it does not tap several factors, which operate in the realistic situation and may reduce memory of some relevant items.…”
Section: Discussionmentioning
confidence: 99%
“…One reason why Japan has been more successful than other countries in using the CIT in crime situations, is that the police are able to better withhold information from the public than in countries like Australia. However, it is worth noting that the effect of the possession of information by innocents is a factor that can be studied and manipulated in the laboratory (e.g., Bradley and Rettinger 1992;Bradley and Warfield 1984), and this work pioneered by Bradley and his colleagues in Canada is continuing in Europe (e.g., Gamer et al 2008), but apparently not in the USA, which is the home of the CQT polygraph, although from the time of its introduction by Lykken (1959), the lab version of the CIT has continued to receive attention from American psychophysiologists (e.g., Allen et al 1992;Iacono et al 1992;Rosenfeld et al 1988). …”
Section: Decrease Of Controlmentioning
confidence: 99%